2021
DOI: 10.26719/emhj.20.125
|View full text |Cite
|
Sign up to set email alerts
|

Views of primary health care providers of the challenges to screening for intimate partner violence, Egypt

Abstract: Background: Health care providers can play an important role in detection of intimate partner violence within health services but barriers exist. Aims: This study aimed to determine the barriers that health care providers in Fayoum, Egypt consider prevent them from screening for intimate partner violence. Methods: This was a cross-sectional study between June 2018 and January 2019. The sample was health care providers (doctors, nurses, social workers and community workers) selected from government primary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
1
6
0
2
Order By: Relevance
“…Similar findings have been reported in Saudi Arabia, Egypt, and Canada, which revealed that gaps in providers’ knowledge and the lack of IPV training are the key factors limiting physicians’ practice of screening. 22 , 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar findings have been reported in Saudi Arabia, Egypt, and Canada, which revealed that gaps in providers’ knowledge and the lack of IPV training are the key factors limiting physicians’ practice of screening. 22 , 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported in Saudi Arabia, Egypt, and Canada, which revealed that gaps in providers' knowledge and the lack of IPV training are the key factors limiting physicians' practice of screening. 22,35,36 Additionally, participants in the present study perceived a variety of workplace challenges that might play a significant role in detecting and dealing with abused women, such as a lack of enough time and private space in their workplace to discuss and assist the victim. This highlights the responsibility of the health institution in providing the appropriate infrastructure and resources for assisting physicians, including local protocols, adequate time, and a private area to deal with abused women.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Previous research showed that dentists without training to manage suspected abuse were less likely to know how to report suspected abuse than those with training [ 35 ]. Also, prior studies including Egyptian physicians [ 30 ] and primary health care workers [ 36 ] similarly showed that health professionals needed training to be familiar with rules and supporting bodies so there seems to be a consensus that this training gap needs to be filled. Training that focuses on promoting positive attitudes towards reporting and increases awareness of existing laws, policies, and agencies in local context may lead to more reporting than training which aims exclusively at increasing the knowledge of the manifestations of abuse and how to identify abuse victims.…”
Section: Discussionmentioning
confidence: 99%